Sweden : Financial Sector Assessment Program Update: Detailed Assessment of Observance on IOSCO Principles and Objectives of Securities Regulation. (IMF Staff Country Reports; Country Report ;, 2011)
This paper provides an assessment of the level of implementation of the International Organization of Securities Commissions (IOSCO) Principles in Sweden's securities market. The assessment has identified several significant weaknesses in the scope and effectiveness of securities market regulation. The Executive Board recommends licensing of insurance intermediaries under the Securities Market Act (SMA). The government should also reconsider its policy of attaching specific short-term project requirements to parliament's annual budget allocation for Finansinspektionen (FI) initially and during the course of the financial year.